Abnormalities of membrane function and lipid metabolism in hypertension: a review - Zicha, J; Kunes, J; Devynck, M A (American journal of hypertension, 1999)
Hypertension, which is characterized by multiple alterations in the structure and function of the cell membrane, is often associated with important metabolic abnormalities including those concerning lipid metabolism. Dyslipidemia accompanying essential hypertension consists of elevated plasma triglycerides, low HDL cholesterol, and increased levels of atherogenic LDL cholesterol particles. The altered membrane microviscosity seen in hypertensive subjects reflects the changes of membrane lipid composition resulting from intensive exchange between circulating and membrane lipids, as well as from abnormal cellular lipid synthesis and metabolism. The changes of membrane microviscosity are known to modulate the activity of proteins involved in ion transport, signal transduction, cell Ca2+ handling, intracellular pH regulation, etc. Alterations in plasma or membrane lipids are indeed closely associated with ion transport abnormalities as well as with impaired control of cytosolic Ca2+ and pH in various forms of hypertension in both humans and rats. Such lipid-dependent modifications of membrane properties in cells participating in the cardiovascular regulation might be a part of pathogenetic mechanisms responsible for chronic blood pressure elevation. Thus nutritional and pharmacologic interventions aiming to normalize abnormal lipid metabolism could be useful for amelioration of membrane abnormalities and lowering of high blood pressure. Future studies of functional membrane alterations in hypertension or dyslipidemia will therefore require the detailed determination of membrane lipid composition and the measurement of microviscosity in particular membrane domains.
Keywords: viskozita krve; sodíko-draslíková ATPasa; Calcium; hypertenze; Cholesterol, LDL; erytrocytární membrána; HDL-cholesterol; LDL-cholesterol; Cholesterol, HDL; vápník; Blood Viscosity; Hydrogen-Ion Concentration; Erythrocyte Membrane; Hypertension; metabolismus lipidů; triglyceridy; koncentrace vodíkových iontů; krysa rodu Rattus; Cell Membrane; Animals; lidé; Sodium-Potassium-Exchanging ATPase; Humans; zvířata; Lipid Metabolism; buněčná membrána; Rats; Triglycerides